Axiological component of text world view (on the samples of Kazakhstani press): Аксиологический компонент текстовой картины мира (на материале казахстанской прессы) - Kozhakhmetova, Assel (Przegląd Wschodnioeuropejski, 2020)
In this article, the authors address the problem of the representation of axiological components regarding modern society based on the material of the Kazakhstani press in Russian. As you know, the media is a kind of barometer of the “mentality” of society. Accordingly, the analysis of newspaper material allows us to judge the formed image of modern society in the axiological consciousness of Kazakhstani people. The purpose of the article is to identify ways and means of verbalizing value and value semantics in the language of the media texts, reflecting the processes of formation of modern Kazakhstani society. As well to make an analysis of axiological components of text world view together with its representation in press. The research being depicted in this paper required the detailed study of newspapers in Kazakhstan and shows its qualitative and quantitative analysis.